Pengaruh Burnout, Disiplin Kerja, Promosi Jabatan Terhadap Kinerja Karyawan (Studi pada Perangkat dan Lembaga Desa Tirtomoyo Kecamatan. Pakis, Kabupaten. Malang) - Masdiki, Eka Ali; Djaelani, Abdul Kodir; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the effect of burnout, work discipline and promotion on the performance of employees in Tirtomoyo Village, Kec. Pakis District Poor. This research used a saturated sampling technique to obtain a sample of 68 respondents who were Tirtomoyo Village employees. The method used in this research is a quantitative method. The results of this research show that the variables burnout and work discipline have a significant effect on employee performance. Meanwhile, job promotions do not have a significant effect on employee performance. Keywords: Effect of Burnout, Work Discipline, Position Promotion, Employee Performance